The research on telemeasuring-controlling and data collection system for greenhouse - YE Sheng; BAO Yi-dan (浙江大学学报. 农业与生命科学版)
Based on the requirement of agriculture automation, after development the microcomputer measuring-controlling system for greenhouse, a telemeasuring-controlling and data collection system was designed. The system consists of two master controllers and their telesend-telereceive controlling instruments, which located in greenhouse and laboratory, and they are connected with telephone wire by their DTMF send-receive modules. The master controllers which located in laboratory controls and collects the environmental parameters of greenhouse by telephone wire.